Law Enforcement Against Parents Perpetrating Physical Violence Against Children Which Causes Death - Beauty Rachmah Yubinas; Kayus Kayowuan Lewoleba (RechtIdee)
This research aims to determine the factors that cause physical violence by parents against children, which causes death, and how law enforcement applies to parents as perpetrators of physical violence against children, which causes death. This research is based on the phenomenon of vulnerability and the increasing cases of physical violence by parents against children, which causes death. Based on Data received throughout 2023 shows 985 instances of physical violence, with 35% of them occurring in the family environment. This research is a normative juridical method with a statutory approach. The results of the study show that the factors causing physical violence against children by parents, which causes death, are children as targets of domestic violence, economic factors, parental personality factors or stress, experiences of violence, and culture in society. The implementation of the Child Protection Law No. 35 of 2014 and the Law on the Elimination of Domestic Violence No. 23 of 2004  is used as a law enforcement effort to prevent criminal acts of physical violence against children which causes death.